Promoting Low-Cost Educational Robotics: A Project-Based Learning Approach for Public High Schools Preparing for the Brazilian Robotics Olympiad - Machado, Filipe de Andrade; Checchia, Jenniffer Oliveira; Mendes, Pedro Henrique Kauan A.; Castro Junior, Amaury Antônio de (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This paper presents a project-based educational initiative designed to promote low-cost robotics in Brazilian public high schools, with a primary focus on preparing students for the Brazilian Robotics Olympiad (OBR). The project integrates concepts from Constructionism and Project-Based Learning to offer hands-on experiences in programming, electronics, and robot assembly using accessible platforms such as Arduino and ThinkerCad. The methodology was implemented over seven sessions and evaluated through formative assessments and student feedback. Preliminary results indicate improvements in students' confidence, problem-solving skills, and engagement with STEM topics. Despite positive outcomes, the study acknowledges limitations related to sample size, lack of control groups, and non-validated assessment instruments. Future work will address these limitations and explore strategies for broader dissemination and impact evaluation.